Gilvimarinus xylanilyticus sp. nov., a novel 1,3-xylanase-secreting bacterium isolated from a marine green alga - Zhang, Yan-Jiao; Sun, Hai-Ning; Xu, Ting-Ting; Zhao, Dian-Li; Yu, Chun-Mei; Zhang, Yi; Zhang, Xi-Ying; Chen, Xiu-Lan; Zhang, Yu-Qiang; Zhao, Fang (Frontiers in Microbiology, 2022)
1,3-xylan, an important organic carbon in the ocean, is peculiar to marine algae. 1,3-xylanase-secreting bacteria and their extracellular 1,3-xylanases play pivotal roles in the degradation and biomass conversion of 1,3-xylan. However, only a few 1,3-xylanase-secreting bacteria and 1,3-xylanases have been reported. Here, we identified a novel marine bacterium capable of secreting 1,3-xylanases, designated as strain HB14T. Phylogenetic analysis revealed that strain HB14T clustered tightly with known species of the genus Gilvimarinus, showing the highest 16S rRNA gene sequence similarity (97.7%) with the type strain of Gilvimarinus chinensis. Based on phylogenetic, genomic, chemotaxonomic and phenotypic studies, strain HB14T was classified as a representative of a novel species in the genus Gilvimarinus, for which the name Gilvimarinus xylanilyticus sp. nov. was proposed. The type strain is HB14T (= CCTCC AB 2022109T = KCTC 92379T). Four 1,3-xylanases secreted by strain HB14T were identified based on genome and secretome analyses, and the two (Xyn65 and Xyn80) with relatively higher abundance in secretome were successfully expressed in Escherichia coli and biochemically characterized. They showed the highest activity at pH 6.0-7.0 and 40°C and released mainly 1,3-xylobiose and 1,3-xylotriose from 1,3-xylan. These data suggest that strain HB14T acts as a player in marine 1,3-xylan degradation and recycling and that its extracellular 1,3-xylanases may have a good potential in 1,3-xylooligosaccharides preparation.